Pengaruh promosi penjualan dan kualitas pelayanan terhadap keputusan pembelian konsumen CV Sukaku Abdi Utama Desa Jambe Tangerang - Marzuki; Sutomo; Novi Irwansyah (Universitas Tangerang Raya, 2023)
The purpose of this study was to determine the effect of sales promotions and service quality on purchasing decisions for consumers of CV Sukaku Abdi Utama. The research method used is a quantitative method. In this study, the independent variables were used, namely Sales Promotion (X1), Service Quality (X2) and the dependent variable, namely Purchase Decision (Y). The object of this study were partners of CV Sukaku Abdi Utama with a total population of 215 partners and sampling using probability sampling technique with random sampling method so that a total sample of 68 respondents was obtained. The results of the study show that sales promotions partially influence purchasing decisions and service quality influences purchasing decisions of CV Sukaku Abdi Utama consumers. The results of the simultaneous variable test have the result that sales promotion and service quality have an influence on the consumer purchasing decision variable by 0.722 or 72.2%, so it can be concluded that there is an influence of 72.2% on the purchase decision can be influenced by Sales Promotion (X1) and Service Quality (X2) and the value of 27.8% is influenced by other factors.